Strategi Pemberdayaan Usaha Kecil dan Menengah - - Sukidjo (Jurnal Ekonomi dan Pendidikan, 2004)
Economic crisis in Indonesia shows that economic development paradigm with trickle down effect strategy, which give a priority to conglomerate economic role is not suitable strategy, since it can not provide strong economic foundation. During economic crisis, conglomerates economic experienced of bankruptcy and negative economic growth; on the contrary small and medium business (enterprise) survived even it was able to lead economic to recovery process. Small and medium business have important role in reducing unemployment, equalizing income distribution, and reducing urbanization rate. However, small and medium business face many problems, such as: lack of capital, marketing limitation, and low quality of human resources and used technology. Considering how important role of small and medium business and many problem faced by them so that it is need to enhance government support.